Studies of jet mass in dijet and W/Z + jet events - Chatrchyan, S.; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Aguilo, E.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Fabjant, C.; Friedl, M.; Fruehwirth, R.; et al. (Springer Science and Business Media LLC, 2013)
Abstract Invariant mass spectra for jets reconstructed using the anti-k T and CambridgeAachen algorithms are studied for different jet “grooming” techniques in data corresponding to an integrated luminosity of 5 fb−1, recorded with the CMS detector in proton-proton collisions at the LHC at a center-of-mass energy of 7 TeV. Leading-order QCD predictions for inclusive dijet and W/Z+jet production combined with parton-shower Monte Carlo models are found to agree overall with the data, and the agreement improves with the implementation of jet grooming methods used to distinguish merged jets of large transverse momentum from softer QCD gluon radiation.
Keywords: Jet mass; Nuclear and High Energy Physics; [PHYS.HEXP] Physics [physics]/High Energy Physics - Experiment [hep-ex]; cms; high energy collider; LHC; CMS; dijet mass; Hadron-Hadron Scattering; FOS: Physical sciences; Observables; Hadron-hadron scattering; Particle physics; Large hadron collider; CMS; High Energy Physics - Experiment; Physics; High Energy Physics - Experiment (hep-ex); Observables; Physics; Jets; [PHYS.HEXP]Physics [physics]/High Energy Physics - Experiment [hep-ex]; info:eu-repo/classification/ddc/530; Fisica delle particelle; Hadron-Hadron Scattering; Nuclear and High Energy Physics; Hadron-Hadron Scattering; CMS; Physics; ddc:530; Física; Large hadron collider; CERN LHC Coll; QC Physics / fizika; Quantum Chromodynamics (QCD); Physique des particules élémentaires; LHC; CMS; HEP; Particle physics; physics; Algorithms